The Formation of Separate Risk Management Committee and the Effect on Modified Audit Report (Malaysian Management Journal, 2013)
The aim of the paper is to examine the formation of a separate risk management committee (RMC) and its effect on the modified audit report among the non-banking and financial companies listed in Bursa Malaysia. Data was collected from the annual reports of a sample of 300 companies from 2004 until 2009. Both descriptive and multivariate analyses were employed to address the research objectives. The results indicate that a separate RMC is negatively related with the acceptance of the modified audit report. Further, the RMC’s members with independent non-executive status and members with accounting and financial background will also probably reduce the acceptance of the modified audit report. However, losses recorded for previous financial years are likely to increase the issuance of modified audit report by the auditor. The period of auditor engagement with the client and client size will also affect the modified audit report. The findings provide empirical evidence on the development and importance of a separate RMC for the modified audit report.